Building a VoIP network with multimedia communication server 5100 - Chaffin, Larry (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2006)
The first book published on deploying Voice Over IP (VoIP) products from Nortel Networks, the largest supplier of voice products in the world. This book begins with a discussion of the current protocols used for transmitting converged data over IP as well as an overview of Nortels hardware and software solutions for converged networks. In this section, readers will learn how H.323 allows dissimilar communication devices to communicate with each other, and how SIP (Session Initiation Protocol) is used to establish, modify, and terminate multimedia sessions including VOIP telephone calls. This section next introduces the reader to the Multimedia Concentration Server 5100, and Nortels entire suite of Multimedia Communications Portfolio (MCP) products. The remaining chapters of the book teach the reader how to design, install, configure, and troubleshoot the entire Nortel product line. If you are tasked with designing, installing, configuring, and troubleshooting a converged network built with Nortel's Multimedia Concentration Server 5100, and Multimedia Communications Portfolio (MCP) products, then this is the only book you need. It shows how you'll be able to design, build, secure, and maintaining a cutting-edge converged network to satisfy all of your business requirements Also covers how to secure your entire multimedia network from malicious attacks.
1. Getting started the MCS5100 Overview 2. MCS5100 Architecture 3. MCP Installation and Configuration 4. Deploying i2004 IP Phones 5. Deploying PC Client 6. Personal Agent Installation and Configuration 7. Deploying Call Pilot 8. Meet Me Conferencing 9. Ad-Hoc Conferencing 10. Wireless IP Phone and PDA Client Overview 11. Securing Nortel VoIP Installations 12. Advanced Configuration and Troubleshooting.
Keywords: Internet telephony; Computer network; Electronic books